1991
DOI: 10.1002/jmv.1890350409
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus RNA in blood donor sera detected by the polymerase chain reaction: Comparison with supplementary hepatitis C antibody assays

Abstract: The low specificity of screening ELISAs for antibodies to hepatitis C virus in blood donors has called for confirmatory tests. Two types of supplementary antibody assays are available, recombinant immunoblot assays (RIBA-1 and RIBA-2) and an antibody consumption test referred to as a neutralization assay. Amplification of viral nucleic acid by the polymerase chain reaction (PCR) provides an antibody independent mode of detecting viral infection. We applied reverse transcription-double PCR to detect an HCV 5'-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 12 publications
1
56
0
Order By: Relevance
“…In addition to the three recombinant antigens mentioned above, this test also utilizes the recombinant protein 5-1-1 and superoxide dismutase (SOD) 27 . Recently, a more sensitive third-generation of RIBA (RIBA-3) has been introduced and uses the same antigens as the EIA-3.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the three recombinant antigens mentioned above, this test also utilizes the recombinant protein 5-1-1 and superoxide dismutase (SOD) 27 . Recently, a more sensitive third-generation of RIBA (RIBA-3) has been introduced and uses the same antigens as the EIA-3.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was used for demonstration of HCV RNA in serum from patients with indeterminate RIBA II reac tions using the method described by Widell et al [14], Retrospective testing of stored serum samples was performed in patients found to be anti-HCV positive for determination of the time of seroconversion to HCV in relation to treatment on dialysis and trans fusions. All patients had been tested regularly for hepatitis B markers during treatment on dialysis, and sera were kept at -20°C during at least 5 years in the laboratory.…”
Section: Hepatitis C Antibody Testingmentioning
confidence: 99%
“…The second thermocycling of the typing PCR consisted of 25 cycles in a Perkin-Elmer thermocycler under stringent conditions as follows: melting at 94°C for 1 min, annealing at 63 °C for 1 min and elongation at 72 °C for 1.5 min. Lastly, the final amplification product was mixed with bromphenol blue, electrophoresed in an agarose gel, stained with ethidium bromide, visualized and photographed as previously de scribed [12].…”
Section: Methodsmentioning
confidence: 99%
“…The viral RNA was extracted from 100 pi of serum using the acid guanidinium thiocyanate-phenol-chlo roform method of Chomczynski and Sacci [11] with some improve ments [12], Water controls were included between each sample and weak-positive controls after every six samples.…”
Section: Methodsmentioning
confidence: 99%